2014
DOI: 10.1515/commun-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Enjoyment of arousing television news: The role of age and sensation seeking

Abstract: This study investigated the role of television news as entertainment by focusing on the enjoyment that viewers experience while watching television news stories. In particular, the study examined the relationship between arousing news stories and enjoyment, and explored the potential moderating role of age and sensation seeking. Participants (N = 288) watched four news stories and reported both their feelings of arousal and their enjoyment of each story. An ∩-shaped relationship between arousal and enjoyment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Grabe, Zhou, Lang, and Bolls (2000) found that negative stories that were packaged in a tabloid style were enjoyed less than negative stories that were packaged in a neutral style. This finding is in accordance with findings by Hendriks Vettehen, Nuijten, and Peeters 2008and Kleemans, Hendriks Vettehen, Eisinga, and Beentjes (2014) that both showed that the arousal that was elicited by sensationalist features was positively related to enjoyment, but only up to a moderate level of arousal. News stories that elicited high levels of arousal (stories that included more arousal eliciting features) were enjoyed less.…”
Section: The Gratifying Potential Of Sensationalist Newssupporting
confidence: 93%
See 2 more Smart Citations
“…Grabe, Zhou, Lang, and Bolls (2000) found that negative stories that were packaged in a tabloid style were enjoyed less than negative stories that were packaged in a neutral style. This finding is in accordance with findings by Hendriks Vettehen, Nuijten, and Peeters 2008and Kleemans, Hendriks Vettehen, Eisinga, and Beentjes (2014) that both showed that the arousal that was elicited by sensationalist features was positively related to enjoyment, but only up to a moderate level of arousal. News stories that elicited high levels of arousal (stories that included more arousal eliciting features) were enjoyed less.…”
Section: The Gratifying Potential Of Sensationalist Newssupporting
confidence: 93%
“…Bailey et al, (2013) found an interaction, indicating that the combination of negative content and tabloid packaging drew longer viewing times than the added effects of negative content and tabloid packaging would suggest. In contrast, the findings from studies on information processing and enjoyment of sensational news would suggest that viewers spend more time on news containing either negative content or tabloid packaging features than on the combination of these, which could induce cognitive overload (Grabe et al, 2000(Grabe et al, , 2003 or overstimulation (e.g., Grabe et al, 2000;Hendriks Vettehen et al, 2008;Kleemans, Hendriks Vettehen et al, 2014). So, an important aim of this study is to investigate whether using sensationalism to stimulate viewing is a matter of "the more, the better" (as suggested by the Bailey et al,'s study) or whether there are limits to the power of sensationalism (as suggested by theory and findings on related variables).…”
Section: Preferences For Sensationalist Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is interesting to note that while we expect the proposed age differences in recall mainly because of cognitive aging, they may be intensified by generational differences. Since the formative years of today's younger adults took place in an arousing, fast-paced media environment in which they encounter rapidly shifting images and absorb visual information quickly (e.g., Oblinger, Oblinger and Lippincott 2005;Tapscott 1998Tapscott , 2008, arousing messages may be more natural to them (Kleemans, Hendriks Vettehen, Eisinga and Beentjes 2014;Tapscott 1998Tapscott , 2008, which is an additional explanation why arousal commercials may be recalled better by younger than by older adults. In sum, we present the following hypothesis:…”
Section: Age Differences In Recall Of Brands and Products In Arousingmentioning
confidence: 99%
“…In other words, at the optimal level of arousal, the audience will like the message most. Zuckerman's (1994) concept of sensation seeking may be helpful in explaining age differences at this optimal level of arousal (Kleemans et al 2014). Optimal arousal levels are supposed to be related to the individual characteristic of sensation seeking, which is the need for varied, novel and complex sensations and experiences (Zuckerman 1994).…”
Section: Age Differences In Liking Of Arousing Commercialsmentioning
confidence: 99%